'I Didn't Want to Write This': The Social Embeddedness of Translating Moonsighting Verses of the Qur'an into Swahili. Issue 3 (October 2015) - van de Bruinhorst, Gerard C.
Abstract: As a result of increasing globalisation the public sphere has expanded over the recent decades. Consequently Qur'an translations increasingly exhibit a highly pluralised concept of religious authority, demonstrating an eclectic use of sources as authors respond simultaneously to local and global discourses. This paper shows how the commentary in a popularising Swahili tafsīr by the preacher Said Moosa al-Kindy on two particular Qur'an verses, Q. 2:185 and Q. 2:189, cannot be understood as the outcome of theological and linguistic considerations only, but rather as a multi-epistemic, socially embedded product. Q. 2:185 and Q. 2:189 are often used to endorse particular viewpoints in East African moon sighting debates. This discourse revolves about the question of whether to accept a crescent sighting report from anywhere in the world to determine the beginning of the lunar month or to wait for a visible moon from a more restricted locality. This paper situates al-Kindy's translation within the wider field of Swahili Qur'an commentaries and compares his treatment of these verses to that in two scholarly products from outside the established genre of tafsīr . One is the polemical discourse on this subject by an Ibadi intellectual writing in Swahili and the second is the lunar calendar and website produced by a Tanzanian book trader. In all three of these works Qur'anic authority is paramount, but if we want to understand the diverse mediations of the Qur'anic message in a specific milieu we should not only look at the influence of exegetical traditions but also focus on social actors and their very personal, localised experiences.